2014
DOI: 10.1039/c4nr03850a
|View full text |Cite
|
Sign up to set email alerts
|

Strong negative nanocatalysis: oxygen reduction and hydrogen evolution at very small (2 nm) gold nanoparticles

Abstract: The electron transfer kinetics associated with both the reduction of oxygen and of protons to form hydrogen at gold nanoparticles are shown to display strong retardation when studied at citrate capped ultra small (2 nm) gold nanoparticles. Negative nanocatalysis in the hydrogen evolution reaction (HER) is reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 45 publications
4
47
0
6
Order By: Relevance
“…Given their generally high stability and amenability to widespread use, such surfaces have been able to produce large amounts of H 2 at rates rivalling those of enzymatic systems and many new examples have recently emerged. 106,107 New developments in this field are instead focused on increasing catalytic selectivity for H 2 evolution over O 2 reduction in order to maximise efficiency. 12,104,105 Their use includes a few disadvantages however, as they have generally low 'per atom activity' and ascertaining the exact nature of the catalytically active site and mechanism can be difficult.…”
Section: Oxygen-tolerant Catalytic Surfacesmentioning
confidence: 99%
“…Given their generally high stability and amenability to widespread use, such surfaces have been able to produce large amounts of H 2 at rates rivalling those of enzymatic systems and many new examples have recently emerged. 106,107 New developments in this field are instead focused on increasing catalytic selectivity for H 2 evolution over O 2 reduction in order to maximise efficiency. 12,104,105 Their use includes a few disadvantages however, as they have generally low 'per atom activity' and ascertaining the exact nature of the catalytically active site and mechanism can be difficult.…”
Section: Oxygen-tolerant Catalytic Surfacesmentioning
confidence: 99%
“…Bulk gold metal shows moderate ORR activity and its activity depends on the size in nanoparticles. For example Crompton and coworkers 36 showed that ultra small (1.5-2nm) citrate capped gold nanoparticles acts as negative catalyst for ORR in compare to Au macro-electrode. It is also reported by them 37 that the 17-40 nm AuNPs showed comparable ORR properties with Au electrode and H 2 O 2 was the final product due to two electron reduction of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…To sustainably consider the globally rapid increasing demand of energy, tremendous efforts are being devoted to advance the technologies for clean and renewable energy conversion [1][2][3][4][5][6][7][8][9][10][11]. Among these green energy approaches, the hydrogen evolution reaction (HER) is attracting significant attention due to its role in electrochemical water splitting and the subsequent use of the generated hydrogen in fuel cells [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…(2)) or the Heyrovsky step (Eq. (3)) depending on the nature of the electrode material [1,2,6,[8][9][10]14,15]. …”
Section: Introductionmentioning
confidence: 99%